INTEGRASI MANAJEMEN RISIKO DAN MAQASHID SYARIAH DALAM PENGAMBILAN KEPUTUSAN STRATEGIS LEMBAGA KEUANGAN SYARIAH - Andesta Susanti (Prodi Manajemen Universitas Syekh Yusuf Al Makassari Gowa, 2026)
This study aims to analyze and develop an integrative model of risk management and maqasid al-shariah in strategic decision-making within Islamic financial institutions. The research employs a qualitative approach with a conceptual design through library research and a systematic literature review of recent scholarly publications. Data were analyzed using content analysis, comparative analysis, and conceptual synthesis to construct an integrative framework. The findings indicate that risk management in Islamic financial institutions extends beyond financial and operational risk mitigation to include sharia compliance risk. Maqasid al-shariah serves as a value-based framework that broadens strategic orientation from mere profitability to social welfare and sustainability. The integration of these two concepts produces a more balanced strategic decision-making model that aligns economic growth, financial stability, and social responsibility. This study contributes theoretically to the development of Islamic strategic management literature and provides practical implications for strengthening governance in Islamic financial institutions.